Reliability and Validity of a New Taekwondo-Specific Change-of-Direction Speed Test With Striking Techniques in Elite Taekwondo Athletes: A Pilot Study - Aloui, Ali; Tayech, Amel; Mejri, Mohamed Arbi; Makhlouf, Issam; Clark, Cain C. T.; Granacher, Urs; Zouhal, Hassane; Ben Abderrahman, Abderraouf (Frontiers in Physiology, 2022)
The purpose of this study was to examine the test-retest reliability, and convergent and discriminative validity of a new taekwondo-specific change-of-direction (COD) speed test with striking techniques (TST) in elite taekwondo athletes. Twenty (10 males and 10 females) elite (athletes who compete at national level) and top-elite (athletes who compete at national and international level) taekwondo athletes with an average training background of 8.9 ± 1.3 years of systematic taekwondo training participated in this study. During the two-week test-retest period, various generic performance tests measuring COD speed, balance, speed, and jump performance were carried out during the first week and as a retest during the second week. Three TST trials were conducted with each athlete and the best trial was used for further analyses. The relevant performance measure derived from the TST was the time with striking penalty (TST-TSP). For absolute reliability, the TST’s typical error of measurement (TEM), 90% compatibility limits, and magnitudes were 4.6 %, 3.4 to 7.7, for males, and 5.4 %, 3.9 to 9.0, for females. The homogeneous sample of taekwondo athletes meant that the TST’s TEM exceeded the usual smallest important change (SIC) with 0.2 effect size in the two groups. The new test showed mostly very large correlations with linear sprint speed (r = 0.71 to 0.85) and dynamic balance (r = -0.71 and -0.74), large correlations with COD speed (r = 0.57 to 0.60) and vertical jump performance (r = -0.50 to -0.65), and moderate correlations with horizontal jump performance (r = -0.34 to -0.45) and static balance (r = -0.39 to -0.44). Top-elite athletes showed better TST performances than elite counterparts. Receiver operating characteristic analysis indicated that the TST effectively discriminated between top-elite and elite taekwondo athletes. In conclusion, the TST is a valid, and sensitive test to evaluate the COD speed with taekwondo specific skills, and reliable when considering ICC and TEM. Although the usefulness of the TST is questioned to detect small performance changes in the present population, the TST can detect moderate changes in taekwondo-specific COD speed.